PENGARUH PENERAPAN MODEL MAKE A MATCH TERHADAP HASIL BELAJAR IPS SISWA KELAS V - Pattingge, Aullery Jordan; Marli, Suhardi; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "how to influence the applicability of the model Make a Match against the learning outcomes Social Science pupils class V 36 State primary school South Pontianak?". This research aims to know the influence of the application of the model Make a Match against the learning outcomes Social Science pupils class V 36 State primary school South Pontianak. This research uses quasi experiment kind of Experiment Method (quasy experimental Design). Experimental design with Non Equivalent Control Group Design. The population in this research is the whole grade V State primary school South Pontianak 36 of 50 students. The sample of this research is the grade V A (experimental class) that add up to 25 students and grade V B (grade control) that add up to 25 students. Instruments for measuring the results of a study of pupils in the form of tests with multiple choice form of as many as 50 reserved. Based on the results of the analysis of data obtained on average post-test a control class and a 69.42 average post-test experiment class of 75.28. Hypothesis test results using a t-test (Saparated variants) obtained thitung = 2.8390 for 48 dk and Î± = 5% obtained t the table of 1.6749, meaning thitung > ttabel (2.8390 > 1.6749), the Ha received. So, it can be concluded that there is an influence of the application of the model to Make a Match to the study of social sciences towards learning outcomes students of class V 36 State primary school South Pontianak. The calculation of effect size (ES), retrieved the ICE of 0.57 (zero comma fifty seven) criteria are. This means the model Make a Match influence (effect) against the results of a study on the material students appreciate the struggles of the characters in maintaining independence in class V 36 State primary school South Pontianak.Â Keywords: Influence, the Model Make a Match, the Results of the Study.